2010
DOI: 10.1029/2009jd013346
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from main propulsion engine on container ship at sea

Abstract: [1] Emission measurements were made for major gases and PM 2.5 mass for a post PanaMax Class container vessel operating on heavy fuel oil at sea. Additional measurements were made for PM composition, elemental and organic carbon, select hydrocarbons, including PAHs, carbonyls, and n-alkanes. The testing followed the International Standard Organization protocols for emission measurements and operating test cycle. Results showed the weighted emission factor for NO x and PM 2.5 were 19.77 ± 0.28 and 2.40 ± 0.05 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 43 publications
14
49
0
Order By: Relevance
“…Agrawal et al (2008) performed exhaust gas measurements inside a container-ships' stack and found a value of f SO 4 = 3.7-5 % (positively correlated with engine load) for a fuel sulphur content of 2.05 %. These results are confirmed by Agrawal et al (2010) (f SO 4 = 2.4-5 % with fuel sulfur content of 3.01 %). Lack et al (2009) measured ship-emission plume compositions within 15 min post-emission and deduced f SO 4 = 1.4 ± 1.1 % and f SO 4 = 3.9 ± 2.0 % for low (< 0.5 %) and high (> 0.5 %) fuel sulphur content, respectively.…”
Section: Methodssupporting
confidence: 77%
“…Agrawal et al (2008) performed exhaust gas measurements inside a container-ships' stack and found a value of f SO 4 = 3.7-5 % (positively correlated with engine load) for a fuel sulphur content of 2.05 %. These results are confirmed by Agrawal et al (2010) (f SO 4 = 2.4-5 % with fuel sulfur content of 3.01 %). Lack et al (2009) measured ship-emission plume compositions within 15 min post-emission and deduced f SO 4 = 1.4 ± 1.1 % and f SO 4 = 3.9 ± 2.0 % for low (< 0.5 %) and high (> 0.5 %) fuel sulphur content, respectively.…”
Section: Methodssupporting
confidence: 77%
“…Figure 13 and Table 4 show emission factors for CO in this study in comparison to other studies in the literature. Emission factors for carbon monoxide (EF CO ) are expected to drop with increasing ship engine load (speed) (Agrawal et al, 2008(Agrawal et al, , 2010Moldanová et al, 2009;Petzold et al, 2011;Jalkanen et al, 2012;Khan et al, 2012b;Cappa et al, 2014). EF CO in this study was in good agreement with other studies for which the vessel speed was very slow.…”
Section: Emission Factorssupporting
confidence: 80%
“…load factors (Agrawal et al, 2008(Agrawal et al, , 2010Lack et al, 2008Lack et al, , 2009Moldanova et al, 2009;Murphy et al, 2009;Petzold et al, 2008Petzold et al, , 2010. Further studies have reviewed and compared emission factors (Buhaug et al, 2009;Dalsøren et al, 2009;Lack and Corbett, 2012).…”
Section: International Shipping and Aviationmentioning
confidence: 99%